Pengembangan E-Modul Ajar Interaktif pada Perkuliahan Pewara Berbasis Alur Merdeka - Noor Cahaya; Rusma Noortyani; Dwi Wahyu Candra Dewi; Arum Murdianingsih; Aulia Novitasari (JURNAL BAHASA, SASTRA, DAN PEMBELAJARANNYA (JBSP), 2026)
The rapid advancement of technology in education necessitates the use of adaptive learning media, particularly in the Pewara course, which emphasizes communication and practical skills. This study aims to examine the potential of using an interactive e-module based on the Merdeka Learning flow (Alur Merdeka) to improve students’ learning outcomes. This study employed a Research and Development (R&D) approach using the ADDIE model in the development phase. The effectiveness of the product was evaluated using a one–group pretest–posttest design involving 69 students from the Department of Indonesian Language and Literature Education. The results indicated an improvement in students’ learning outcomes, with an average score increase of 26.20. The paired sample t-test yielded a significance value of 0.000 (p < 0.05), indicating a statistically significant difference between pretest and posttest scores. These findings suggest a change in learning outcomes following the use of the interactive e-module. However, these results should be interpreted with caution, as the study did not involve a control group. Therefore, the observed improvement in learning outcomes cannot be fully attributed to the use of the e-module. Accordingly, these findings represent preliminary evidence of the potential of the e-module to support learning in the Pewara course.